HOW THE PROHIBITION OF HATE SPEECH AND DEFAMATION’S SOCIAL MEDIA CONTENT BE ENFORCED IN INDONESIA - Mahardika, Alfian; Firdaus, Nuraemy; Fauziah, Syifa (PEOPLE: International Journal of Social Sciences, 2019)
Legal Aspect of the Freedom of expression was fundamental human rights which was now a concern with the action Monitoring and screening access to information and heavy surveillance application that eventually break the privacy rights of the netizens by government apparatus, whether those acts are done by law or against the law. Freedom of expression was a state authority and its enactment needs to be using Pancasila values in accordance with the law of Law No.11 of 2008 on Information and Electronic Transactions. While ensuring to access information, any citizen could use actualize themselves and express opinions without hatred towards society. This legal research was made using the juridic-normative approach with the secondary data by legal literature study with analyzing between legislation applicable to legal theories and important practices of positive law which will be discussed. This legal research to find out about the regulation of freedom of expression on social media according to law and regulation and the application in Indonesia. This study needs to be developed and discussed in more detail the freedom of expression in social media. The right to freedom of expression was one of the important features of a democratic country that upholds the high sovereignty of the people to realize the implementation of that state well, and the state has jurisdiction to determine, apply, and judge upon anyone who damages Pancasila. Freedom of expression through social media was a fundamental human right that must be protected. However, in the case of the fulfilment of rights, there will also be an obligation to respect the rights of others, the exercise of those rights may be decided by law. Various cases of freedom of expression through social media become a process of enforcing this Human Rights. Prevention by education from government and private sectors were needed in other to decrease the hate speech and defamation’s content in social media.